2020
DOI: 10.3847/1538-4357/ab6605
|View full text |Cite
|
Sign up to set email alerts
|

Current Population Statistics Do Not Favor Photoevaporation over Core-powered Mass Loss as the Dominant Cause of the Exoplanet Radius Gap

Abstract: We search for evidence of the cause of the exoplanet radius gap, i.e., the dearth of planets with radii near 1.8R ⊕. If the cause were photoevaporation, the radius gap should trend with proxies for the early-life high-energy emission of the planet-hosting stars. If, alternatively, the cause were core-powered mass loss, no such trends should exist. Critically, spurious trends between the radius gap and stellar properties arise from an underlying correlation with instellation. After accounting for this underlyi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 36 publications
2
45
1
Order By: Relevance
“…Instead, the amount of mass lost depends on the equilibrium temperature of the planet. Simulations of core-powered mass loss from Loyd et al (2020) produce a radius gap that is comparable to the the radius gap observed in the data, differing only in location. This may be explained by differences in stellar mass, though they find no stellar mass dependence on the exoplanet radius gap of their sample.…”
Section: Atmosphere Retentionsupporting
confidence: 68%
“…Instead, the amount of mass lost depends on the equilibrium temperature of the planet. Simulations of core-powered mass loss from Loyd et al (2020) produce a radius gap that is comparable to the the radius gap observed in the data, differing only in location. This may be explained by differences in stellar mass, though they find no stellar mass dependence on the exoplanet radius gap of their sample.…”
Section: Atmosphere Retentionsupporting
confidence: 68%
“…The red lines show atmosphere retention thresholds after 3.0 Gy for the case where all volatiles are in the atmosphere initially and there is no primary atmosphere; the 16th and 84th percentiles are shown, for varying XUV flux (by ±0.4 dex, 1 σ; ref. 48) relative to the baseline model following the results of refs. 49 and 50 (SI Appendix, section 1a).…”
Section: Gj 357bmentioning
confidence: 99%
“…Regardless, this gap has been noted in both the Kepler (Fulton et al 2017) and K2 (Hardegree-Ullman et al 2020) planet samples, indicating that an underlying formation mechanism is at play. As we continue to increase the known planet sample, we will be able to better constrain the underlying mechanism (Loyd et al 2020).…”
Section: Deviations From the Modelmentioning
confidence: 99%